Die Sprachkontaktphänomene im Deutschen der masurischen Altgläubigen Zusammenfassung - Jorroch, Anna (Die deutsche Sprache in vielfältigen Forschungsparadigmen. Beiträge polnischer Doktoranden anlässlich der 9. Linguistischen Tagung–Łódź, 09.05.2015, 2016)
The phenomenon of the language contact in the German of the Masurian old-believers. The aim of this article is to present some aspects of the research done into the contact induced changes in the German language still spoken by the old-believers in Masuria. This region was part of Germany (Prussia) until 1945, so the Russian refugees, who had come in 1830 to Masuria, were exposed to German culture and learned the German language. After the Second World War, in 1945 the area of East-Prussia was divided between Russia and Poland. Masuria, the south part of East-Prussia, was annexed to Poland. The old-believers in Masuria, born before the end of the 1950’s, can speak three languages: The Russian dialect of the old-believers living in Poland, Polish and German, which is the object of the author’s research. The religion of the old-believers, the past influence of German culture and language and the present contact with Polish have lead to an interesting linguistic combination, which is their trilingual language competence. Old-believers pray in old-Church Slavonic and talk with each other in German, Polish and their Russian dialect. This article is going to present the influences in the field of interferences in the German language, the negotiation mechanism as well as the triplicate code-switching.